Aus der Bibliothek des ehemaligen Deutschen Entomologischen Instituts. Korrespondentenliste vom Nachlaß Germar, Halle. - Marwinski, Felicitas (Contributions to Entomology = Beiträge zur Entomologie, 1971)
A list of correspondents was compiled from the papers left by coleopterologist Ernst Friedrich Germar (1786-1853) which are now in former Deutsches Entomologisches Institut.